Fabrication of a Lateral Heterostructure of Crystallized MoO2/Amorphous MoO3‐x for Photothermal Conversion. Issue 5 (25th March 2020) - Guo, Cang; Wei, Cong; Shen, Yonglong; Cui, Xinwei; Xu, Qun
Abstract: The heterostructure of crystallized MoO2 /amorphous MoO3‐x was firstly constructed via reduction of crystalline MoO3 by Mo metal via a hydrothermal method. All characterization results indicate the coexistence of a defective crystallized MoO2 phase and amorphous MoO3‐x phase. Furthermore, the heterostructure products possess excellent photothermal conversion (61.5%). Abstract : A heterostructure of crystallized MoO2 /amorphous MoO3‐x was constructed via reduction of crystalline MoO3 by Mo metal via a hydrothermal method. The heterostructure possesses an excellent photothermal conversion performance (61.5%).